From Indicators to Insights: Measuring Urban Quality of Life in Medium-Sized Greek Cities with the DPRD-20 Urban Indicator System - Psatha, Eva (European Journal of Geography, 2025)
Urban Quality of Life (UQoL) is a critical concept in urban studies, capturing the well-being of city residents through environmental, social, and economic conditions. This study refines the existing DPRD-50 system—originally developed to assess UQoL in Greek cities—by applying Principal Component Analysis (PCA) to the indicator dataset from its first application ten years ago. This process resulted in the DPRD-20 system, a more concise and flexible tool for comparative urban analysis. Beyond improving usability, the new system enables a longitudinal comparison of UQoL across time, revealing how selected Greek cities have evolved over the past decade. The findings highlight significant differences: cities like Ioannina, Volos, and Heraklion perform well due to strengths in healthcare, cultural amenities, or sustainable mobility. In contrast, cities like Kavala and Kalamata face infrastructure challenges despite strong environmental assets. The research underscores the importance of benchmarking as a means for cities to learn from each other, while supporting data-driven governance through an open-source monitoring framework with broader relevance to the European urban context. Highlights: Development of a new urban indicator system, through PCA, based on the existing DPRD-50 framework. Use of open-source data to assess Urban Quality of Life in Greek medium-sized cities. Benchmarking tool for supporting evidence-based urban policies and cross-city comparisons.